Common Property, Congestion, and Environmental Pollution - Haveman, Robert H. (Quarterly Journal of Economics, 1973)
Journal Article Common Property, Congestion, and Environmental Pollution Get access Robert H. Haveman Robert H. Haveman University of Wisconsin Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 87, Issue 2, May 1973, Pages 278–287, https://doi.org/10.2307/1882188 Published: 01 May 1973